Pulmonary Disease due to Mycobacterium tuberculosis in a Horse: Zoonotic Concerns and Limitations of Antemortem Testing - Konstantin P. Lyashchenko; Rena Greenwald; Javan Esfandiari; Alexis Lecu; W. Ray Waters; Horst Posthaus; Thomas Bodmer; Jean-Paul Janssens; Fabio Aloisio; Claudia Graubner; Eléonore Grosclaude; Alessandra Piersigilli; et al. (Veterinary Medicine International)
A case of pulmonary tuberculosis caused by Mycobacterium tuberculosis was diagnosed in a horse. Clinical evaluation performed prior to euthanasia did not suggest tuberculosis, but postmortem examination provided pathological and bacteriological evidence of mycobacteriosis. In the lungs, multiple tuberculoid granulomas communicating with the bronchiolar lumen, pleural effusion, and a granulomatous lymphadenitis involving mediastinal and tracheobronchial lymph nodes were found. Serologic response to M. tuberculosis antigens was detected in the infected horse, but not in the group of 42 potentially exposed animals (18 horses, 14 alpacas, 6 donkeys, and 4 dogs) which showed no signs of disease. Diagnosis of tuberculosis in live horses remains extremely difficult. Four of 20 animal handlers at the farm were positive for tuberculous infection upon follow-up testing by interferon-gamma release assay, indicating a possibility of interspecies transmission of M. tuberculosis.